ANTIBREAST CANCER ACTIVITY OF NANOPROPOLIS INDONESIA ON INDUCED MAMMARY GLAND TUMOR BY DMBA IN VIRGIN SPRAGUE–DAWLEY RATS - Akhmad Endang Zainal Hasan; Djumali Mangunwidjaja; Titi Candra Sunarti; Ono Suparno; Agus Setiyono (BIOTROPIA, 2016)
The objective of this study was to determine the effect of nanopropolis on DMBA-induced mammary tumors in rats. After the first tumor appearance, twenty-eight rats were divided into seven groups. Groups 1, 2, and 3 served as recipients of nanopropolis treatments at dosages of 8, 32, and 56 μg/mL, respectively. Group 4 received propolis at 233 μg/mL, Group 5 served as the treatment control, Group 6 received DMBA only, and Group 7 served as the normal control. The effects of nanopropolis at 32 μg/mL and propolis at 233 μg/mL were similar in reducing tumor size, healing wounds caused by the tumor, and eliminating cancer cells. Furthermore, the study suggested a relationship between particle size of the absorbent material and its effectiveness. Overall, nanopropolis was very effective in treating mammary gland tumors and breast cancer even at small concentrations.